Kesetiaan Merek Vs Perilaku Berpindah: Apakah Kecenderungan Untuk Berpindah, Persepsi Kemudahan Penggunaan, Dan Persepsi Resiko Mampu Membentuk Perilaku? - Kusuma Ningrum, Nonik (Universitas PGRI Yogyakarta, 2019)
AbstractPurpose - This study is aimed to examine the effect of propensity to switch, perceived ease of use, and perceived risk on brand loyalty and switching behavior.Design/methodology/approach - Utilizing purposive random sampling, a number of 100 customers of 36 brands of 12 product categories were asked to fill in the questionnaire as primary survey data. To analyze the measurement model, structural model, and the good fit model, this study made use of the structural equation model.Findings - Propensity to switch significantly positive affects brand loyalty and switching behavior; whereas perceived of ease of use significantly positive affects brand loyalty and significantly negative affects switching behavior; and perceived risk significantly negative affects brand loyalty and significantly positive affects switching behaviorResearch limitation - A more numbers of respondents and more variations of respondents’ background should be considered for future study. A propensity to be a loyal customer variable should also be added in the model.Originality/value - This study takes a look at two different points of views of customer behaviors, those are customers who remain to stay with one brand and those are who always seek for something new and keep switching.